Zhodnocení kontaminace půd v oblasti Valašského Meziříčí - Dunajská, Sabina (Vysoké učení technické v Brně. Fakulta chemická, 2023)
Tato práce se zabývá kontaminací půdy způsobenou těžkými kovy v oblasti Valašského Meziříčí. Analyzovanými kovy byly kadmium, chrom, měď, železo, rtuť, mangan, nikl, olovo, zinek. Kovy byly stanoveny ve 34 odebraných vzorcích. Analýzy byly provedeny pomocí metod AMA-254 a AAS. K vyhodnocení kontaminovaných míst byly použity indexy znečištění a dále byly posouzeny zdravotní rizika.

This thesis deals with soil contamination caused by heavy metals in the region of Valašské Meziříčí. The metals analysed were cadmium, chromium, copper, iron, mercury, manganese, nickel, lead, zinc. Metals were determined in 34 samples. The analyses were performed using AMA-254 and AAS methods. Contamination indices were used to assess the contaminated sites and health risks were also assessed.
Assessment of contamination in selected locations of Valašské Meziříčí
Keywords: Kontaminace půdy; těžké kovy; indexy znečištění; ekologické indexy; zdravotní rizika; Valašské Meziříčí; AAS; Soil contamination; heavy metals; pollution indices; ecological indices; health risks; Valašské Meziříčí; AAS